MODEL SEBARAN SPASIAL DAN KESESUAIAN HABITAT SPESIES INVASIF MANTANGAN (Merremia peltata (L.) Merr.) DI TAMAN NASIONAL BUKIT BARISAN SELATAN - Hermawan, Rudi; Hikmat, Agus; Prasetyo, Lilik Budi; Setyawati, Titiek (Universitas Nusa Bangsa, 2017)
Some of conservation area is invaded by some invasive species like Merremiapeltata in Bukit Barisan Selatan National Park. The aim of this study is to identify the distribution and habitat characteristics ofÂ M. peltata, as well as building a model of the spatial distribution and habitat suitability ofÂ M. peltata Tampang Resort, BBSNP. The research was conducted at Resort Tampang, BBSNP, from March to May 2014. For modeling, have been used 9 independent variables, like distance from the road, distance from the garden, elevation, slope, aspect, surface temperature, Normalized Difference Index (NDVI), Normalized Moisture Index (NDMI), and Forest Canopy Density (FCD). Modeling process that have been done with binary logistic regression used GIS-based modeling.The result of habitat suitability analisys show that the most suitable habitat for M. peltata at the Tampang Resort BBSNP is at elevation of 0-100 meters above sea level, slope 8-15%, aspect 90-180degrees, distances from the road >800 meters, distance from the garden/human activities >800 meter, surface temperature <260C, NDVI values between 0.42-0.62, NDMI value between 0.3-0.4, and FCD value between 50-75%. The results of validation test shows that model can predict 96.87% of M. peltata presence, and 50% of M. peltata absence at Tampang Resort, BBSNP.